Penerapan Model Pembelajaran SSCS (Search, Solve, Create and Share) Terhadap Kemampuan Berpikir Kritis Siswa - Erlistiani, Mifta; Syachruroji, A.; Andriana, Encep (Jurnal PGSD, 2020)
The purpose of this research to know the critical thinking ability of the students that using SSCS model. The method used in this research is Kuasi Experiment with the research design Nonequivalent Control Group Design. The research was conducted at SD Negeri Kesaud in academic year 2018/2019. The technique were taken used purposive sampling. In this research, VA class was used as the experiment class and the VB class was used as the control class. The purpose of data analysis techniques to testing the hypotheses using two test and using the right side test. Based on the calculation hypothesis of two parties obtained a score of -2,010 ? 4,599 ? 2,010 if–ttabel ? thitung ? ttabel then H0 is rejected and Ha is accepted. The result of this research can be concluded that the critical thinking ability of students applied the SSCS (Search, Solve, Create and Share) model is better than that of students who applied the Direct Intruction model.